Same-day discharge protocol for laparoscopic treatment of adnexal disease: management and acceptance. Issue 3 (1st March 2022) - Bazzurini, Luca; Manfredi, Gianfranco; Roldán, Eugenia Tomás; Peiretti, Michele; Basso, Silvia; Preti, Eleonora; Garbi, Annalisa; Franchi, Dorella; Zanagnolo, Vanna; Ceppi, Lorenzo; Landoni, Fabio
Abstract: Objective: Develop a 'same-day discharge' setting for laparoscopic treatment of adnexal disease. Setting: Preventive Gynecology, European Institute of Oncology, Milan, Italy. Population: Two hundred patients undergoing laparoscopic procedures. Material and methods: Data were retrospectively collected through clinical, surgical and laboratory reports. After discharge patients were contacted by phone and e-mail. Main outcome measures: The rate of discharge, adverse events and readmission was measured. The need for adjunctive care provided by our on-call service or by a primary care physician and the acceptability of the same-day discharge protocol were also investigated. Results: One hundred and sixty-five patients out of 200 were discharged on the same day. Of the 35 patients hospitalized, the most frequent causes for overnight admission were: uncontrolled pain, surgical length or complexity of the procedure in nine patients, nausea/vomit in four patients. One hundred and one out of 200 patients answered the mailed questionnaire. None of the discharged patients were readmitted. Eighty-five percent of the answering patients evaluated the length of their hospital stay as adequate or moderately adequate. Ninety-two percent of the patients would recommend the day surgery to other patients. Conclusions: our experience demonstrates that the same-day discharge protocol for laparoscopic treatment of adnexal disease is safe and acceptable.